Smartphone: an asset in medical education and health care in the era of COVID-19 pandemic-our perspective - Jhirwal, Manisha; Sharma, Charu; Shekhar, Shashank; Meena, Satya Prakash (International Journal Of Community Medicine And Public Health, 2021)
The COVID-19 cases are increasing rapidly and the government across the world has imposed the social distancing along with maintaining good hygiene. The infection with corona virus ranges from mild common cold to acute respiratory illness leading to morbidity and mortality.1 There is no specific treatment for COVID-19 infection except the preventive measures like social distancing, lockdown etc.2 To maintain social distancing so as to curb the spread of disease, schools and colleges were closed long back since March 2020. Online classes took over the conventional classroom teaching.